GAMES KaDoKo AND COOKING CLASS IN CHEMISTRY, FOR WHAT? - Asworo, Yuliana Dwi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2024)
Abstract The development of science, technology and art requires human resources to be able to compete globally in the 21st century. The effects of the Covid-19 pandemic require digitalization of education so that learning activities continue without limitations in space and time. Colloidal systems are part of chemistry, examples of which are often found in everyday life. The complexity of the material in the colloid system in the form of memorization, usually carried out by teachers using lecture and discussion methods, makes teachers innovate how to make learning activities in the classroom fun and memorable so that the learning material is understood in accordance with the demands of the basic competencies that students must master, both aspects cognitive and psychomotor, namely KD 3.14 and KD 4.14. One way to make chemistry learning activities in class meaningful is to do practicums and play. In this research, the author conducted qualitative research with a descriptive approach through colloidal domino game (KaDoKo) using an inquiry method carried out in groups, then each student wrote down questions along with explanations of the answers in a notebook. For the skills domain, students carry out cooking practice (cooking class), namely making colloid products or food preparations made from colloids, then presenting the manufacturing process, the type of colloid produced and the final result in video as a form of digitalization of education carried out by students. The teacher ensures that the type of colloid made by each group is different to ensure product variations. The final result obtained is that students enjoy learning activities and gain a different learning experience compared to previous learning and have directed communication skills based on the products they have made related to the concept of colloid systems and there is an increase in mastery of colloid concepts compared to the previous year. Abstrak Perkembangan ilmu pengetahuan, teknologi dan seni menuntut sumber daya manusia untuk mampu bersaing secara global di abad ke-21 ini. Efek pandemi Covid-19, menuntut digitalisasi pendidikan agar kegiatan pembelajaran tetap berlangsung tak terbatas ruang dan waktu. Sistem koloid merupakan bagian dari ilmu kimia yang contohnya sangat banyak ditemukan dalam kehidupan sehari-hari. Kompleksitas materi dalam sistem koloid yang berupa hafalan, biasanya dilakukan guru dengan metode ceramah dan diskusi membuat guru berinovasi bagaimana caranya membuat kegiatan pembelajaran di kelas berlangsung menyenangkan dan berkesan agar materi pembelajaran dipahami sesuai dengan tuntutan dalam kompetensi dasar yang harus dikuasai peserta didik, baik itu aspek kognitif maupun psikomotoriknya yaitu KD 3.14 dan KD 4.14. Salah satu cara agar kegiatan pembelajaran kimia di kelas menjadi bermakna adalah melakukan praktikum dan bermain. Dalam penelitian ini penulis melakukan penelitian kualitatif dengan pendekatan deskriptif melalui game domino koloid (KaDoKo) menggunakan metode inkuiri yang dilakukan per kelompok, lalu setiap peserta didik menuliskan soal beserta penjelasan jawabannya di buku catatan. Untuk ranah keterampilan, peserta didik melakukan praktik memasak (cooking class) yaitu membuat produk koloid atau olahan makanan berbahan dasar koloid kemudian mempresentasikan proses pembuatan, jenis koloid yang dihasilkan dan hasil akhirnya dalam bentuk video sebagai bentuk digitalisasi pendidikan yang dilakukan peserta didik. Guru memastikan jenis koloid yang dibuat setiap kelompok berbeda jenisnya agar terjadi variasi produk. Hasil akhir yang diperoleh adalah peserta didik menikmati kegiatan pembelajaran dan mendapatkan pengalaman belajar yang berbeda dibanding pembelajaran sebelumnya serta memiliki kemampuan berkomunikasi yang terarah berdasarkan produk yang telah dibuatnya terkait konsep sistem koloid serta terjadi peningkatan penguasaan konsep Koloid dibandingkan tahun sebelumnya.